Schema Perpetuation and Schema Healing: A Case Vignette for Schema Focused Therapy in Islamic Perspective - Khalily, Muhammad Tahir (Islamic Studies, 2012)
This paper analyses a traditional approach used by a Sufi saint for healing the characterological problems and integrates it with the currently available approach popularly known as Schema Focused Therapy. For this purpose an anecdote of an individual suffering from chronic characterological problems that had inflicted devastating affects on him and on the society at large has been explored. All the traditional methods of corrections, characterized to punitive measures, failed to ameliorate his maladaptive behaviour. However, he bumped into a faith healer who used an integrated approach of behavioural change and cognitive restructuring with emotional support in a subtle way, which became a turning point in his life. He was enabled to rebuild his personality through the induction of healthy schema and appropriate coping style.